Development of formative assessment tool for a primary, technology classroom - RR, Swathi; Fox-Turnbull, Wendy; Earl-Rinehart, Kerry; Calder, Nigel (Design and Technology Education: An International Journal, 2020)
Teachers and students' interactions in the classroom include a large number of questions, some of which are a key part of formative assessment. Questions can lead to an extended dialogue between the teacher and the student, potentially facilitating a better understanding of the students' conceptions and providing teachers with information to guide student learning. Technology Observation and Conversation Framework (TOCF) was identified as a framework of questions specially designed for a technology classroom. In this qualitative, design-based research, the TOCF was modified for alignment with the New Zealand curriculum and provided to two primary teachers teaching ages 9-10. The version of TOCF reported in this article was developed through an iterative process in an authentic environment. The teachers were interviewed periodically, and modifications were made to the format of the framework. The findings in this paper focus on the outputs of the iterative process and the feedback given by the teachers on the TOCF. While teachers in the study found the questions crucial to deepen student thinking in technology, they faced some constraints in using the TOCF in the classroom. The findings suggest that any introduction of a new resource should proceed slowly in the classroom and time needs to be given for increasing familiarity with the new resource. It is also possible that inexperienced teachers could find adoption of questioning practice quite tricky and would need to be supported extensively to change their practice.